Cohesion Policy – The Litmus Test of the European Future - Emil Boc (Transylvanian Review of Administrative Sciences, 2024)
Europe is the winner of the Cohesion Policy. It is vital that the model of shared management, multi-level governance, and partnership remains the guiding principle of the Cohesion Policy beyond 2027. Subsidiarity and a place-based approach are crucial; we can’t afford to lose the territorial dimension. There is no future for this policy without a strong role of cities and regions. If you try to replace it with a centralized instrument as a top-down Recovery and Resilience Facility, you will destroy the very essence of the Cohesion Policy. The Cohesion Policy is working on the ground, and it must be maintained, in a modernized way. The Cohesion Policy must continue to be the single policy to address the challenges inherent to cohesion in Europe. That includes supporting a just transition in all regions and supporting all territories so that they can take advantage of the single market. That includes supporting all regions so that the EU can be more competitive at a global level. Cohesion Policy is a solution, not a problem!